Analisis Kualitatif Pelayanan dan Kinerja Keuangan Perusahaan CV. Indi karya Teknik pada Masa Pandemi Covid-19 - Allya Dewi Listyani; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study was conducted with the aim of analyzing service quality and financial performance during the Covid-19 period at CV. Indi Karya Teknik. On financial performance through analysis of profitability ratios and liquidity ratios. The model in the research conducted is based on field research, analysis of financial statements and determining the level of comparison of the profitability index and liquidity index analysis during the covid 19 pandemi. The results of this study indicate that many changes can be made to analyze service quality in the pandemi era that can be viewed from employee performance, namely on five service dimensions, namely reliability, responsiveness, assurance, empathy, and evidence directly during the Covid-19 pandemi. Company resumes are displayed to analyze financial performance in calculating profitability, including return on equity and return on total assets. CV. Indi Karya Teknik is on the rise from 2020 to 2021. The calculation of the current ratio can be seen from the total assets/current assets and short-term liabilities for 2020 and 2021 showing good financial performance along with a decrease in short-term liabilities from 2020 to 2021.Keywords: Service Quality, Profitability Ratio Analysis, Liquidity Ratio Analysis and Financial Performance.